Restoring anatomical and functional integrity of human corneal endothelium after large Descemet’s membrane tear (clinical case) - S. V. Trufanov; S. A. Malozhen; E. A. Pivin (Oftalʹmologiâ)
is case report describes Descemet’s membrane tear occurred during phaco. Early post-op corneal edema involved optical zone. 1-month treatment was ineffective, and the patient was referred to endothelial keratoplasty. Considering that corneal endothelium is able to cover local Descemet’s membrane defects if endothelial cell density is initially high, we decided to postpone endothelial keratoplasty and to observe the patient. Topical medications included osmotic, antiinflammatory, and hypotensive agents. 2 months after phaco, corneal edema began to reduce. 4 months after phaco, the cornea was almost transparent. Endothelial cell density in the central zone (where Descemet’s membrane was absent) was 1002 cells/mm2. The cornea remained transparent for 2-year observation. In a year after phaco, visual acuity was 20/32. Post-op bullous keratopathy treatment provided good therapeutic and optical outcome. Complete resolution of corneal edema due to Descemet’s membrane tear that persisted for 4 months after complicated cataract surgery demonstrates the possibility to recover structural integrity and functions of corneal endothelium even in large Descemet’s membrane tears. In corneal edema due to mechanical injury, endothelial keratoplasty should be performed at least 3 or 4 months after the injury since endotheliocyte function recovery is possible if endothelial cell density is initially high.